EARLY HOME CARE ERRORS AND THE IMPACT ON DELAY IN HOSPITAL FOR PATIENTS WITH CORONARY HEART DISEASE - Rosjidi, Cholik Harun (University of Muhammadiyah Malang, 2020)
Introduction: Heart disease is a major problem in public health lately. Delay in treatment is still a major problem in managing coronary heart disease. Objective: The purpose of this study was to analyze the pre-hospital care of a heart attack and its relationship with the delay to the hospital. Method: The study was conducted at Dr. Hardjono Ponorogo Regency, a representative sample of 108 respondents was taken purposively. The cross-sectional analytic design was conducted to measure the relationship between pre-hospital care and delay to the hospital. Analysis of the chi-square test with ? = 0.05 was used to test the association between pre-hospital care and its relationship with the delay in the hospital for coronary heart disease patients. Result: The results of the study illustrate that there were 70.4% of families doing first aid in the wrong category, and there were 73.1% of families late in bringing CHD patients to the hospital. There was a significant relationship between behavior with patient delay to the hospital (p = 0.000). There was a significant relationship between behaviors with patient delay in the hospital. Discussion: The promotion of early signs of heart disease should be focused on the level of the family as well as integrated emergency care services immediately implemented to reduce the delay in coronary heart disease patients to the hospital.